The association between workloads and health hazard among delivery riders in China - Mao, Ai-Lin; Tian, Chun-Miao; Liu, Chen-Xi (Frontiers in Public Health, 2025)
IntroductionDrawing on the extended job demands-resources model, this study aims to identify the primary occupational health risks affecting delivery riders and explore mechanisms between workload and illness.MethodsA respondent-driven sampling method was employed to minimize data bias. A total of 1,092 riders in Beijing, Shanghai, and Jinan participated in the survey. Logit regression analysis was conducted to assess the associations and mechanisms were also analyzed.ResultsA significant positive relationship was observed between the number of daily deliveries and daily working hours with reported illness. This association was more significant among riders who are primary family breadwinners or who work part-time.ConclusionExcessive workload negatively affects the health of delivery riders. Overwork may heighten riders’ risk perception, which can ultimately lead to illness. However, this relationship can be mitigated if delivery platforms implementing measures to reduce work-related pressure. A key practical implication of this study is the urgent need for platform companies to assume greater responsibility in labor protection, particularly in curbing the tendency toward overwork.